Låsning till spolkarslock - Hedén, Niclas (Sektionen för ekonomi och teknik (SET), 2012)
Since 2007, I´ve been working in the steel industry in a place called “SSAB”. That’s why itseemed right to contact them for this thesis.The SSAB concern is global, but SSAB Sweden involves raw steel producing in Luleå, heavyplate producing in Oxelösund, and sheet metal producing in Borlänge.